The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acs.jpclett.1c02040
|View full text |Cite
|
Sign up to set email alerts
|

P Doping Promotes the Spontaneous Visible-Light-Driven Photocatalytic Water Splitting in Isomorphic Type II GaSe/InS Heterostructure

Abstract: The development and design of clean and efficient water splitting photocatalysts is important for the current situation of energy shortage and environmental pollution. A new type of isomorphic GaSe/InS heterostructure is constructed, and the optoelectronic properties were studied through first-principles calculations. The results show that GaSe/InS vdW heterostructure is a type II semiconductor with a band gap of 2.09 eV. However, through the analysis of the energy band edge position and Gibbs free energy chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 65 publications
(87 reference statements)
2
13
0
Order By: Relevance
“…The MoSH monolayer exhibits metallic behavior, while the MoSi 2 N 4 monolayer shows semiconducting characteristic with a band gap of 1.81/2.38 eV, which is comparable with that of the experimental measurement of 1.94 eV, confirming the reliability of our calculations. Generally, it is obvious that the HSE06 method predicts a more accurate band gap of semiconductors. , However, the PBE band gap of the MoSi 2 N 4 monolayer is closer to the experimental band gap than the HSE06 method. Thus, we used the PBE method to calculate all the calculations.…”
mentioning
confidence: 90%
“…The MoSH monolayer exhibits metallic behavior, while the MoSi 2 N 4 monolayer shows semiconducting characteristic with a band gap of 1.81/2.38 eV, which is comparable with that of the experimental measurement of 1.94 eV, confirming the reliability of our calculations. Generally, it is obvious that the HSE06 method predicts a more accurate band gap of semiconductors. , However, the PBE band gap of the MoSi 2 N 4 monolayer is closer to the experimental band gap than the HSE06 method. Thus, we used the PBE method to calculate all the calculations.…”
mentioning
confidence: 90%
“…6(b), by using the formulas w Ga2SeS = E vac À E SC C and IP Ga2SeS = E vac À E SC V , respectively. 70 The carrier mobility is a parameter that is essential for efficiency in electronic, 71-73 photovoltaic 74,75 and photocatalytic [76][77][78] applications. However, most semiconductors have low carrier mobilities, 79 which restrict their feasibility in nano-electronic applications.…”
Section: A Structural Analysis and Electronic Properties Of The Prist...mentioning
confidence: 99%
“…Also, there is a negative correlation between effective mass and carrier mobility, i.e., a small (high) effective mass indicates a high (small) carrier mobility. 76,78 We listed the essential parameters required to find carrier mobility (effective mass (m*) and deformation potential (E 1 )), and in-plane stiffness (C 2D,x ) in Table 3. For monolayer Ga 2 SeS, as expected the hole effective mass is found to be larger than the electron effective mass due to the flat-like VBM (see Fig.…”
Section: A Structural Analysis and Electronic Properties Of The Prist...mentioning
confidence: 99%
“…Zhu et al found that GaN/Zr 2 CO 2 heterostructure has a promising application in tunable high-performance optoelectronic nanodevices due to its large conduction band offset (CBO) and tunable band gap ( Zhu et al, 2021 ). Zhang et al proved that P-GaSe/InS isomorphous heterostructure has excellent performance as a photocatalytic and water splitting material ( Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%